Teachers Preparedness on Implementation of Competence Based Curriculum in Lower Public Primary Schools in Kilifi and Nandi Counties, Kenya - Chemagosi, Mary Jebii (International Journal of Scientific Research and Management (IJSRM), 2020)
The competency based curriculum was introduced in Kenya in 2016 as pilot study for the new curriculum but adapted in 2019 in all pre-schools and lower primary school levels. The curriculum is viewed as a panacea in solving problems of unskilled school leavers with knowledge based to practical based curriculum. The objective of the study was to establish teachers’ preparedness on implementation of competence based curriculum in lower public primary schools in Kilifi and Nandi counties, Kenya. The study used descriptive research design. Data was collected by use of questionnaire, interview schedule and observation schedule. The sample used was 48 head teachers, 48 teachers that were purposively selected. A pilot study was conducted in two schools one from each of the two Counties to pre-test the instruments. The study made use of teachers’ questionnaire, head teachers interview schedule and observation schedule to collect and analyse data from the participants. Validity was ensured by face and content validity while Split-half technique ensured reliability. The quantitative and qualitative data were simultaneously analysed in order to triangulate the findings of the study. The results shows that the overall model is significant (F=6.006, p0.05).This implies that teacher preparedness significantly influence implementation of competency based curriculum and therefore the hypothesis that there is no significant difference between teachers’ preparedness and implementation of competency based curriculum was rejected. The study recommended that the Ministry of education to ensure teachers are equipped with requisite skills, knowledge and teaching and learning resources to adequately prepare teachers for competency based curriculum.